Terapi Relaksasi Dzikir dapat menurunkan Kecemasan pada Ibu Perimenopause - Satriadi, Satriyadi; Saimi, Saimi (Jurnal Kesehatan Qamarul Huda, 2024)
Perimenopause is a natural transition in a woman's life that usually occurs several years before menopause. During perimenopause, the body undergoes major hormonal changes, including decreased production of reproductive hormones such as estrogen and progesterone. This stage is very difficult for perimenopausal mothers to experience because of physical changes that affect a person's appearance, body functions, and psychology. One solution to reduce anxiety levels is to use the dhikr relaxation therapy method. The purpose of this study was to determine the effect of dhikr relaxation therapy on anxiety levels in perimenopausal mothers. The method used in this study was a pre-experimental design with one group pre-test-post-test. Simple random sampling technique was used as a sampling technique and obtained 80 respondents. The results of this study analysis showed a change after 7 days of dhikr relaxation therapy reaching Sig (2-tailed) = 0.000 which means that anxiety levels decreased significantly after the intervention. dhikr relaxation therapy. Conclusion: Dhikr therapy can reduce stressors and anxiety in perimenopause.